Biased interpretations of ambiguous bodily threat information in adolescents with chronic pain. Issue 3 (March 2017) - Heathcote, L.C.; Jacobs, K.; Eccleston, C.; Fox, E.; Lau, J.Y.F.
Abstract : Abstract: Adult patients with chronic pain are consistently shown to interpret ambiguous health and bodily information in a pain-related and threatening way. This interpretation bias may play a role in the development and maintenance of pain and disability. However, no studies have yet investigated the role of interpretation bias in adolescent patients with pain, despite that pain often first becomes chronic in youth. We administered the Adolescent Interpretations of Bodily Threat (AIBT) task to adolescents with chronic pain (N = 66) and adolescents without chronic pain (N = 74). Adolescents were 10 to 18 years old and completed the study procedures either at the clinic (patient group) or at school (control group). We found that adolescents with chronic pain were less likely to endorse benign interpretations of ambiguous pain and bodily threat information than adolescents without chronic pain, particularly when reporting on the strength of belief in those interpretations being true. These differences between patients and controls were not evident for ambiguous social situations, and they could not be explained by differences in anxious or depressive symptoms. Furthermore, this interpretation pattern was associated with increased levels of disability among adolescent patients, even after controlling for severity of chronic pain and pain catastrophizing. The current findings extend our understanding of the role and nature of cognition in adolescent pain, and provide justification for using the AIBT task in longitudinal and training studies to further investigate causal associations between interpretation bias and chronic pain. Abstract : Supplemental Digital Content is Available in the Text.Adolescents with chronic pain were less likely to believe benign interpretations of ambiguous bodily-threat information than controls. This interpretation style was associated with more disability.